2010
DOI: 10.1159/000319623
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane Protects against Acute Kidney Injury in a Small-Size Liver Transplantation Model

Abstract: Background: Living donor liver transplantation (LDLT) patients run the risk of developing acute kidney injury (AKI) and subsequent chronic kidney disease, affecting morbidity and mortality. Sevoflurane has anti-inflammation properties, and renal ischemia/reperfusion under sevoflurane anesthesia resulted in drastic improvements in renal function. Extrahepatic metabolism of sevoflurane has been reported in patients undergoing liver transplantation, and might lead to nephrotoxicity. However, whether sevoflurane a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 54 publications
(46 reference statements)
3
33
0
Order By: Relevance
“…[8][9][10] Many studies have demonstrated that sevoflurane can modulate inflammatory cascades and has protective effects against ischemia/reperfusion injury. [11][12][13] Studies by Suter et al 11 demonstrated a decrease in the production of inflammatory proteins in alveolar epithelial cells with sevoflurane preconditioning in endotoxin-induced lung injury.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Many studies have demonstrated that sevoflurane can modulate inflammatory cascades and has protective effects against ischemia/reperfusion injury. [11][12][13] Studies by Suter et al 11 demonstrated a decrease in the production of inflammatory proteins in alveolar epithelial cells with sevoflurane preconditioning in endotoxin-induced lung injury.…”
Section: Introductionmentioning
confidence: 99%
“…Both propofol and sevoflurane are anti-inflammatory agents because they decrease the production of the nuclear transcription factor (NF-kB) 15,22, which is considered a transcriptional inducer of pro-inflammatory interleukins, such as interleukins 1 and 6 23 and of NGAL itself 24. Through different mechanisms, both sevoflurane and propofol exert protective effects on the kidneys: propofol decreased the tissue damage caused by oxidative stress 25 and in renal ischemia models, sevoflurane provided pharmacological preconditioning 15,26. However, there has been no consensus in the literature regarding the more effective drug for kidney protection.…”
Section: Discussionmentioning
confidence: 99%
“…Though different mechanisms, both propofol 14 and sevoflurane 15 have appeared to reduce renal injury in clinical-surgical and experimental injury models. Various markers are measured serially to monitor kidney injury during the perioperative period, but many of these markers are delayed, or they have sensitivity limitations.…”
Section: Introductionmentioning
confidence: 99%
“…A study of sevofl urane eff ects on renal function in rats after liver transplantation demonstrated signifi cantly reduced NGAL concentrations in the sevofl urane group, as well as smaller epithelial necrosis. In the group anesthetized with sevofl urane, signifi cantly lower serum concentrations of TNF-a, IL-6, and myeloperoxidase were found 2 hours after reperfusion 23 . In parallel with the increase in the number of studies demonstrating the protective role of sevofl urane against the occurrence of AKI, there is also a large number of studies on the protective eff ects of other anesthetics, such as propofol, with regard to AKI.…”
Section: Modulation Of Ischemia/reperfusion Injury and Anti-infl Ammamentioning
confidence: 94%